Penyuluhan Penggunaan Obat yang Benar (Dagusibu) dan Pengelolaan Obat di Rumah Tangga Masyarakat Bumi Mondoroko Raya Malang - Nailis Syifa'; Alvina Arum Puspitasari; Ahmad Shobrun Jamil (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Insufficient public knowledge about appropriate medication use, storage, and disposal practices poses significant health risks and environmental hazards. This community service program sought to enhance understanding of the Dagusibu concept (obtain, use, store, dispose) among PKK mothers in Bumi Mondoroko Raya, Singosari, Malang. The intervention employed pre-test questionnaires, interactive presentations, and question-and-answer sessions involving 13 participants. Pre-test findings revealed substantial misconceptions: eight participants (62%) perceived paracetamol solely as an antipyretic, four participants (31%) deemed household waste disposal acceptable for all expired medications, and three participants (23%) believed antibiotics were available for purchase at local stalls. Following the educational intervention and discussion sessions, participants demonstrated accurate identification of paracetamol's multiple therapeutic indications, appropriate disposal protocols for expired medications, and prescription requirements for antibiotic acquisition. The program successfully enhanced community knowledge regarding rational medication use and household pharmaceutical management. Educational leaflets were disseminated as follow-up materials, with plans established for ongoing monitoring of household medication storage practices.